Prevalence of vitamin D deficiency in 157 boys with duchenne muscular dystrophy. (29th September 2015) - Munot, P; Krishnakumar, D; Robb, S; Davies, T; Muntoni, F; Manzur, A
Abstract : Introduction: Boys with Duchenne muscular dystrophy (DMD) have low bone density. Although corticosteroids improve muscle strength and function in boys with DMD, potential adverse effects include osteoporosis and vertebral fractures. Bianchi et al 1 reported low Vitamin D levels in a small cohort of boys with DMD. The optimal 25-OH vitamin D levels in children have been redefined by Misra et al 2 with the recommendation that serum 25-OH vitamin D level <37.5 nmol/litre constitutes vitamin D deficiency and a level greater than 50 nmol/l is indicative of sufficiency. In the UK there are no large studies to establish vitamin D levels in children with DMD. Objectives: To establish the prevalence of vitamin D deficiency in boys with DMD. Methodology: The North Star neuromuscular network consensus is to check vitamin D levels prior to starting corticosteroid therapy. Data on vitamin D levels was retrospectively collected from the case records through the north star neuromuscular database. Results: 25-OH vitamin D levels were available in 157 boys with DMD. The mean age at checking vitamin D level was 6.9 years (1.5–15.5). Vitamin D levels ranged from 4–155 mol/litre. Alkaline phosphatase was low or normal in all. Clinical rickets was not diagnosed in any of these boys. Among those with levels > 50 nmol/L, at least 2/28 were on supplements. Conclusion: 78% of boys who were tested had inadequate vitamin D levels according to current standards and 15% had severe deficiency. These data have important implications for optimising bone health and for corticosteroid treatment in DMD.